The Synergicity Of Essentially The Identity Of God In The Vedic Teaching And The Siwatattwa As Guidelines For Hindureligious Practices In Bali - I Wayan Ardhi Wirawan; I Gede Sura; Ketut Wardana (Jurnal Penelitian Agama Hindu, 2020)
This research aims to study the essential synergy of divine identity in the Vedic scriptures and the Siwatattwa teachings. The divine identity which is the focus of this research is based on the reason for the development of the discourse "Back to the Veda" as a source of guidelines for Hindu practice in Bali. In this regard, this study focuses on the identity of divinity as a constructive symbol that carries the core teachings of Hinduism. This study was designed in an interpretive qualitative method using a comparative model of the two sources of divine teachings in general, namely the Vedic Scriptures and the Siwatattwa teachings. Novelties which related to the results of this research is that divine identity is essentially contained in the Vedic scriptures and in the Siwatattwa teaching has synergy. The transcendent divine identity in the two sources of Hinduism is abstract, which is beyond the senses and the mind. The divine identity in the immanent dimension is symbolized by name and form as the center of concentration for Hindus in living the existence of the power of” Brahman” or” Ida Sang Hyang Widhi Wasa” in accordance with ista dewata (the embodiment of the revered god). The appreciation of divinity in Balinese-Hindu society uses the source of guidance for the Siwatattwa teachings in the implementation of Hinduism which is sourced from the Vedic scriptures, both sruti and smrti. This phenomenon is the basis for the development of the synergy of divine identity in the Vedic scriptures with the Siwatattwa teaching. In this regard, the appreciation of the divine aspects of Balinese Hindus who use the source of the guidance for the Siwatattwa teachings has also implemented Veda teachings.